The public health consequences of disasters - Noji, Eric K. (Oxford University Press, 1997)
This book summarizes the most recent and useful information about the public health impact of natural and man-made disasters. It emphasizes the uses of epidemiologic knowledge about different types of disasters. Each chapter is based on a variety of experiences and literature drawn from both developing and industrialized countries.